No ------------------------------------------------ 4/5 = (4×2)/(5×2) = 8/10 8 ≠ 3 → 8/10 ≠ 3/10 → 4/5 ≠ 3/10
4/5 ÷ 3/10 = 8/3 or 22/3
2/5 - 3/10 = (2×2)/(5×2) - 3/10 = 4/10 - 3/10 = (4-3)/10 = 1/10.
4/10 + 1/5 = 2/5 + 1/5 = 3/5
If: 3x/4 -5 = x/3 +10 Then: x = 36
No ------------------------------------------------ 4/5 = (4×2)/(5×2) = 8/10 8 ≠ 3 → 8/10 ≠ 3/10 → 4/5 ≠ 3/10
4/5 - 3/10 = 8/10 - 3/10 = 5/10 = 1/2
3/10 - 4/5 = 3/10 - 8/10 = -5/10 = -1/2
4/5 ÷ 3/10 = 8/3 or 22/3
3/5 = 6/10 6/10 and 4/10 are not equivalent.
3/5 + 2/4 = 6/10 + 5/10 = 11/10
2/5 - 3/10 = (2×2)/(5×2) - 3/10 = 4/10 - 3/10 = (4-3)/10 = 1/10.
4/5 - 2/10 = 4/5 - 1/5 = 3/5
To add 2/5 and 3/10, we need to find a common denominator. The least common multiple of 5 and 10 is 10, so we can rewrite 2/5 as 4/10. Adding 4/10 and 3/10 gives us 7/10. Therefore, 2/5 + 3/10 = 7/10.
2/5 divided by 3/10 equals .4/.3 which equals 4/3 or 1.33333333
(2/3) / (4/5) = (2/3) * (5/4) = 10/12 = 5/6
5/10 x 3/4 = (5x3)/(10x4) = 15/40 = 3/8